Epidemiological research on diabetic nephropathy at global, regional, and national levels from 1990 to 2021: an analysis derived from the global burden of disease 2021 study - Zhang, Lu; Jiang, Liangliang; Xu, Rong; Zhang, Xuemei; Zhang, Boxun; Yue, Rensong (Frontiers in Endocrinology, 2025)
ObjectiveA comprehensive assessment of the disease burden is essential for developing effective strategies to address diabetic nephropathy. This study investigates the long-term global trends and epidemiological characteristics of diabetic nephropathy.MethodsData on diabetic nephropathy from the Global Burden of Disease (GBD) 2021 were utilized to evaluate morbidity, mortality, disability-adjusted life years (DALYs), and the impact of the Socio-Demographic Index (SDI). Global risk attribution was assessed, and the Bayesian Age–Period–Cohort (BAPC) model was applied to forecast the future burden of diabetic nephropathy.ResultsIn 2021, there were 107.6 million prevalent cases of diabetic nephropathy globally (95% UI: 99.2–116.0), with an age-standardized prevalence rate of 1,259.6 per 100,000 population (95% UI: 1,162.0–1,359.9), representing a 5.1% decline since 1990. Global deaths attributed to diabetic nephropathy in 2021 reached 477.3 thousand (95% UI: 401.5–566.0), with an age-standardized mortality rate of 5.7 per 100,000 (95% UI: 4.8–6.8), reflecting a 37.8% increase since 1990. The number of DALYs attributable to diabetic nephropathy was 11,278.9 thousand (95% UI: 9,682.8–13,103.9), with an age-standardized DALY rate of 131.1 per 100,000 (95% UI: 112.8–152.5), indicating a 24% rise since 1990.ConclusionsOver the past three decades, the global age-standardized prevalence of diabetic nephropathy has declined, while age-standardized mortality and DALY rates have increased. Significant disparities exist in prevalence, incidence, and DALY rates across regions and countries. The SDI exerts a notable influence on diabetic nephropathy prevalence, underscoring the importance of sustained and enhanced management of risk factors to prevent and treat this condition. Diabetic nephropathy remains a critical global health challenge moving forward.